A rare case of idiopathic multiple small bowel strictures in Indian subcontinent: a case report - Dwivedi, Garima; Singla, Sanjeev Kumar; Virmani, Rohit (International Surgery Journal, 2021)
Small bowel ulcers and strictures are uncommon but when they occur they can be an important cause of morbidity. We reported a case of a multiple strictures in small bowel that was treated surgically pain for 15 years. She also had hypoalbuminemia and iron deficiency anemia. A diagnosis of small bowel stricture was made on CT and surgery was advised. Resection of the 100 cm long segment of small bowel was done. Approximately 10 smooth strictures were identified in the resected segment. Histology did not identify any specific cause. A 43 year old Indian female was diagnosed with subacute small bowel obstruction. She had a history of chronic abdominal pain for 15 years. She also had hypoalbuminemia and iron deficiency anemia. A diagnosis of small bowel stricture was made on CT and surgery was advised. Resection of the 100 cm long segment of small bowel was done. Approximately 10 smooth strictures were identified in the resected segment. Histology did not identify any specific cause. Subacute small bowel obstruction can be associated with various factors. Multiple idiopathic small bowel strictures can be considered as one of the causes. In present case no cause of ulcers and strictures could be found. Idiopathic multiple bowel strictures with fecalith is rare. Histopathology and other investigations revealed no specific cause. We recorded no postoperative complications 2 months after surgery by resection and anastomosis.